2006
DOI: 10.1086/500948
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor κB and Nuclear Factor κB in Granulocyte‐Macrophage Colony‐Stimulating Factor Antagonism of Dexamethasone Suppression of the Macrophage Response toAspergillus fumigatusConidia

Abstract: Background. The dexamethasone (DEX) immunosuppressive effect on macrophage killing activity and cytokine production in response to Aspergillus fumigatus conidia is antagonized by granulocyte-macrophage colony-stimulating factor (GM-CSF). The molecular mechanism is unknown. We postulated that this antagonism is mediated by inhibitor kB (IkB) induction by DEX and is opposed by acceleration of IkB degradation by GM-CSF with or without conidia stimulation, with corresponding effects on translocation and activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…3, network C). Our Ingenuity analysis results support the importance of NF-B in aspergillosis immunity, as reduced nuclear NF-B translocation in macrophages was previously implicated in increased susceptibility to infection following dexamethazone treatment (54), and in sepsis (55). Our data are also consistent with a role for both NF-B and p38 MAPK in dendritic cells following contact with A. fumigatus (56).…”
Section: Discussionsupporting
confidence: 87%
“…3, network C). Our Ingenuity analysis results support the importance of NF-B in aspergillosis immunity, as reduced nuclear NF-B translocation in macrophages was previously implicated in increased susceptibility to infection following dexamethazone treatment (54), and in sepsis (55). Our data are also consistent with a role for both NF-B and p38 MAPK in dendritic cells following contact with A. fumigatus (56).…”
Section: Discussionsupporting
confidence: 87%
“…For vaccinated immunosuppressed animals, the inhibited effector cell could receive a strong local stimulus (cytokines) delivered by a fungus-recognizing, vaccine-primed CD4 ϩ T cell. Similarly, it was shown that treatment with granulocyte macrophage colony-stimulating factor can reverse the immunosuppressive effect of dexa- methasone by enhancing degradation of IB (14). A T-cellderived cytokine stimulus such as IFN-␥ could likewise lead to activation of IB kinases (IKK) in the effector cell (45), to an extent that even increased numbers of corticosteroid-induced IB molecules become sufficiently phosphorylated and degraded.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, cortisone acetate leads to longer (7 days) macrophage suppression, compared with approximately 4 days of suppression noted with dexamethasone [37]. GM-CSF restores steroid-induced loss of antifungal microconidia activity by augmenting proinflammatory cytokine production by alveolar macrophages [37] and by enhanced degradation of inhibitor kappa B and by relegating nuclear factor kappa B translocation [38]. Similarly, mononuclear cell response to fungal hyphal damage is abrogated by dexamethasone treatment; GM-CSF can reverse this effect by supplementing superoxide anion release and monocytemacrophage-assisted damage to Aspergillus fumigatus hyphae [39,40].…”
Section: Gm-csfmentioning
confidence: 97%
“…Furthermore, dexamethasone has been show to compromise macrophage antifungal activity by induction of inhibitor kappa B and via blocking translocation and activation of nuclear factor kappa B [38]. Interestingly, cortisone acetate leads to longer (7 days) macrophage suppression, compared with approximately 4 days of suppression noted with dexamethasone [37].…”
Section: Gm-csfmentioning
confidence: 99%